Forward to the past?: interpreting contemporary and future loyalist violence, 1994-2006 - Monaghan, Rachel (UK Data Service, 2008)
This research project considered in detail loyalist violence in Northern Ireland since the paramilitary ceasefires of 1994, and its potential to continue, especially in relation to possible constitutional changes. The research examined three strands of contemporary loyalist violence, namely: sectarian attacks; violence directed at other loyalists; and the potential for future violence given constitutional uncertainty. The project gathered in-depth information on loyalist violence, including documentary factual research, covering the type of incident, prevalence, location and concentration. From this, geographic information system (GIS) maps of Troubles-related deaths attributed to loyalist paramilitaries were generated. Focus groups and interviews were conducted with loyalist and other key community representatives to ascertain perceptions of loyalist violence. Additional in-depth interviews were also undertaken with groups and individuals from projects and activities aimed at diluting the rationale of paramilitary involvement. Interviews with voluntary groups and statutory agencies allowed further exploration of perceptions of such violence and the potential impacts of diversionary schemes.